Pengaruh Organizational Culture terhadap Job Performance melalui Knowledge Sharing - Ariyani, Lintang Ayu; Frianto, Agus (Jurnal Ilmu Manajemen, 2024)
This research aims to analyze and determine the influence of organizational culture on work performance through sharing knowledge at PT Swabina Gatra Gresik. This research is causality research with a quantitative approach. The sampling technique used saturation techniques, namely 126 employees of PT Swabina Gatra Gresik. The statistical analysis used in this research is structural equation modelling (SEM) with the help of AMOS 24 software. The results of this study explain that organizational culture has a significant positive effect on work performance, organizational culture has quite a large positive effect on knowledge sharing, knowledge sharing has no significant impact on work performance, and knowledge sharing cannot mediate the relationship between organizational culture and performance. Job performance. Companies must always strive to improve the job performance of company employees by continuing to implement an excellent organizational culture. These changes can increase employee productivity so employees can complete work optimally per predetermined standards. Companies can pay more attention to the details of employees' work, always guide and develop employees to have high initiative and create an open and supportive work environment where employees feel comfortable voicing new ideas and completing work quickly to improve performance and minimize errors. Companies must also strive to increase knowledge sharing by implementing a good organizational culture, so these changes are expected to maximize employee interest in knowledge sharing.